2018
DOI: 10.1002/uog.19179
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient vs outpatient management and timing of delivery of uncomplicated monochorionic monoamniotic twin pregnancy: the MONOMONO study

Abstract: In uncomplicated monoamniotic twins, when compared with outpatient management, inpatient surveillance is associated with similar fetal mortality. After 31 6/7 weeks there were no intrauterine fetal deaths or neonatal deaths even up to 36 6/7 weeks. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 31 publications
1
15
0
2
Order By: Relevance
“…A recent meta-analysis showed that inpatient monitoring had a 3% risk of IUD (95% CI 1.4-5.2%), where outpatient management had a higher IUD risk of 7.4% (95% CI 4.4-11.1%) 67 . However, a multicentre cohort study observed no significant difference in perinatal mortality between the inpatient and outpatient managed groups of MCMA twins (adjusted OR 0.21, 95% CI 0.04-1.17) 68 . Recommendations on timing of birth have varied between 32-36 weeks.…”
Section: Controversies In the Management Of Mcma Twin Pregnanciesmentioning
confidence: 92%
“…A recent meta-analysis showed that inpatient monitoring had a 3% risk of IUD (95% CI 1.4-5.2%), where outpatient management had a higher IUD risk of 7.4% (95% CI 4.4-11.1%) 67 . However, a multicentre cohort study observed no significant difference in perinatal mortality between the inpatient and outpatient managed groups of MCMA twins (adjusted OR 0.21, 95% CI 0.04-1.17) 68 . Recommendations on timing of birth have varied between 32-36 weeks.…”
Section: Controversies In the Management Of Mcma Twin Pregnanciesmentioning
confidence: 92%
“…The primary outcome was intrauterine fetal death. 42 Out of 195 pregnancies (390 fetuses), the overall perinatal loss rate was 10.8% (peak fetal death rate at 29 weeks of gestation, reaching 4.3%). From 32 0/7 to 36 6/7 , no fetal or neonatal deaths were recorded.…”
Section: Timing Of Deliverymentioning
confidence: 99%
“…The perinatal mortality of MCMA twin pregnancies is high and ranges from 10% to 40% 57,58,62,63 . However, recent data suggest a rate of about 10%, resulting from a better prenatal diagnosis, repeated fetal monitoring, and elective preterm delivery 64 …”
Section: Umbilical Cord Abnormalities Related To Monochorionic Twin G...mentioning
confidence: 99%
“…The Monochorionic Monoamniotic (MONOMONO) study also reported that fetal monitoring is essential to achieve good outcomes in MCMA pregnancies, regardless of the surveillance setting. 64 In 2020, the Society for Maternal-Fetal Medicine(SMFM) Special Statement published a checklist for managing MCMA pregnancies that featured serial ultrasound starting from 16 weeks of gestation; every two weeks for the assessment of amniotic fluid volume and bladder filling, and every two to four weeks for the evaluation of fetal growth. A detailed fetal anatomy survey should be performed at 18 to 22 weeks of gestation (or earlier if technically feasible) and a fetal echocardiogram should be performed at 18 to 22 weeks of gestation.…”
Section: Umbilical Proximate Cord Insertion (Pci)mentioning
confidence: 99%